Cultivable hydrocarbon degrading bacteria have low phylogenetic diversity but highly versatile functional potential. (August 2019) - Barbato, Marta; Mapelli, Francesca; Crotti, Elena; Daffonchio, Daniele; Borin, Sara
Abstract: Hydrocarbon (HC) pollution is a threat to the marine environment and bioremediation strategies based on microbial degradation have been developed for pollution clean-up. Effectiveness of bioaugmentation, i.e. the addition of suitable HC-degrading microorganisms to the polluted matrix, strongly depends on the metabolic and physiological versatility of cultivable HC-degrading microorganisms and on their adaptation capacity. The aim of this work was to investigate the potential of laboratory enrichment approaches to obtain cultivable HC-degrading bacteria having versatility breadth. Despite we used as inoculum marine samples of different origin and contamination history, and applied different enrichment strategies, we brought into culture 183 hydrocarbonoclastic bacterial strains strongly dominated by only the two genera Alcanivorax and Marinobacter . These isolates, screened for traits related to HC degradation, biostimulation and abiotic stress tolerance, demonstrated nevertheless to have a diverse functional potential, correlated to the adopted enrichment strategy. Although the obtained strains resulted phylogenetically similar, we showed that multiple cultivation approaches enhanced their metabolic diversification with potential benefits for bioaugmentation effectiveness. Highlights: Physiological diversity of microbial isolates is needed for bioagumentation set up. Alcanivorax and Marinobacter are common isolates from HC contaminated environments. Diverse hydrocarbon enrichment strategies select bacteria with functional versatility.